Subtraction-free and bisulfite-free specific sequencing of 5-methylcytosine and its oxidized derivatives at base resolution - Liu, Y; Hu, Z; Cheng, J; Siejka-Zielinska, P; Chen, J; Chen, J; Inoue, M; Ahmed, A; Song, C (Springer Nature, 2021)
Although various methods have been developed for sequencing cytosine modifications, it is still challenging for specific and quantitative sequencing of individual modification at base-resolution. For example, to obtain both true 5-methylcytosine (5mC) and true 5-hydroxymethylcytosine (5hmC) information, the two major epigenetic modifications, it usually requires subtraction of two methods, which increases noise and requires high sequencing depth. Recently, we developed TET-assisted pyridine borane sequencing (TAPS) for bisulfite-free direct sequencing of 5mC and 5hmC. Here we demonstrate that two sister methods, TAPSβ and chemical-assisted pyridine borane sequencing (CAPS), can be effectively used for subtraction-free and specific whole-genome sequencing of 5mC and 5hmC, respectively. We also demonstrate pyridine borane sequencing (PS) for whole-genome profiling of 5-formylcytosine and 5-carboxylcytosine, the further oxidized derivatives of 5mC and 5hmC. This work completes the set of versatile borane reduction chemistry-based methods as a comprehensive toolkit for direct and quantitative sequencing of all four cytosine epigenetic modifications.